FORMATION OF PROFESSIONAL COMPETENCE OF STUDENTS BY MEANS OF PRACTICALLY-ORIENTED INTERACTIVE LEARNING - Kobets, В.М. (Journal of Information Technologies in Education (ITE), 2013)
In the paper practical-oriented interactive teaching methods of economists, such as mind mapping, case method and information technologies of teaching are analyzed.